Aging of intrauterine tissues in spontaneous preterm birth and preterm premature rupture of the membranes: A systematic review of the literature. Issue 9 (September 2015) - Polettini, J.; Dutta, E.H.; Behnia, F.; Saade, G.R.; Torloni, M.R.; Menon, R.
Abstract Background Many adverse pregnancy outcomes (APOs), including spontaneous preterm birth (PTB), are associated with placental dysfunction. Recent clinical and experimental evidences suggest that premature aging of the placenta may be involved in these events. Although placental aging is a well-known concept, the mechanisms of aging during normal pregnancy and premature aging in APOs are still unclear. This review was conducted to assess the knowledge on placental aging related biochemical changes leading to placental dysfunction in PTB and/or preterm premature rupture of membranes (pPROM). Methods We performed a systematic review of studies published over the last 50 years in two electronic databases (Pubmed and Embase) on placental aging and PTB or pPROM. Results The search yielded 554 citations, 30 relevant studies were selected for full-text review and three were included in the review. Only one study reported oxidative stress-related aging and degenerative changes in human placental membranes and telomere length reduction in fetal cells as part of PTB and/or pPROM mechanisms. Similarly, two animal studies reported findings of decidual senescence and referred to PTB mechanisms. Conclusion Placental and fetal membrane oxidative damage and telomere reduction are linked to premature aging in PTB and pPROM but the risk factors and biomolecular pathways causing this phenomenon are not established in the literature. However, no biomarkers or clinical indicators of premature aging as a pathology of PTB and pPROM have been reported. We document major knowledge gaps and propose several areas for future research to improve our understanding of premature aging linked to placental dysfunction.